2021
DOI: 10.3390/toxins13120858
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Production and Characterization of a New Toxin from Cryptops iheringi Centipede Venom Revealed by Proteome and Transcriptome Analysis

Abstract: Among the Chilopoda class of centipede, the Cryptops genus is one of the most associated with envenomation in humans in the metropolitan region of the state of São Paulo. To date, there is no study in the literature about the toxins present in its venom. Thus, in this work, a transcriptomic characterization of the Cryptops iheringi venom gland, as well as a proteomic analysis of its venom, were performed to obtain a toxin profile of this species. These methods indicated that 57.9% of the sequences showed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Cryptopsi heringi centipede belongs to Cryptops genus it synthesize and secrete novel putative toxin Cryptoxin-1. Its recombinant form promote edema in mice footpads with massive neutrophils infiltration [56].…”
Section: Proteome and Transcriptome Analysismentioning
confidence: 99%
“…Cryptopsi heringi centipede belongs to Cryptops genus it synthesize and secrete novel putative toxin Cryptoxin-1. Its recombinant form promote edema in mice footpads with massive neutrophils infiltration [56].…”
Section: Proteome and Transcriptome Analysismentioning
confidence: 99%
“…In the last 30 years, with the highly developed methods of venom research, including cDNA library construction, protein sequencing, mass spectrometry, genomic analysis, transcriptome analysis, proteome analysis, and structural biology techniques, venoms from many animals have been intensively studied [ 15 , 16 ]. Recently, a new venom-peptide family named HAND toxins and a recombinant toxin named Cryptoxin-1 from centipedes were successively identified [ 17 , 18 ]. Centipede venoms have recruited gene families by horizontal gene transfer between bacteria, fungi, and oomycetes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The venom of snakes was approached in different aspects as the structural and functional variability in the composition of venoms from individual snakes [1], the mechanisms of action of whole venoms [2,3], the mechanisms of action of individual components as crotoxin [4], phospholipases A2 [5], metalloproteinases [6][7][8], and the oral immunity induced by whole venoms and their components [9]. Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16]. The great potential for molecules derived from animal venoms as drug leads was also reviewed [17], and the antimicrobial [18], anticoagulant [19,20], and analgesic [21,22] effects have been highlighted in original studies reported here.…”
mentioning
confidence: 99%